A single-dose intranasal live-attenuated codon deoptimized vaccine provides broad protection against SARS-CoV-2 and its variants - Liu, Xiang; Ng, Wern Hann; Zusinaite, Eva; Freitas, Joseph; Taylor, Adam; Yerragunta, Venugopal; Aavula, Shukra Madhaha; Gorriparthi, Sambaiah; Ponsekaran, Santhakumar; Bonda, Rama Lakshmi; Mani, Priyanka; Nimmagadda, Sridevi V.; et al. (Nature communications, 2024)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2, COVID-19) continues its significant health and economic impact globally. Despite the success of spike-protein vaccines in preventing severe disease, long-lasting protection against emerging variants and the prevention of breakthrough infections and transmission remain elusive. We generate an intranasal live-attenuated SARS-CoV-2 vaccine, CDO-7N-1, using codon deoptimization. CDO-7N-1 shows highly attenuated replication and minimal or no lung pathology in vivo over multiple passages. It induces robust mucosal and systemic neutralizing antibody and T-cell subset responses, in mice (female K18-hACE2 and male HFH4-hACE2 mice), hamsters, and macaques triggered by a single immunization. Mice and hamsters vaccinated with CDO-7N-1 are protected from challenge with wild-type (WT) SARS-CoV-2 and other variants of concern. Serum from vaccinated animals neutralizes WT SARS-CoV-2, variants of concern (beta and delta), variants of interest (omicron XBB.1.5) and SARS-CoV-1. Antibody responses are sustained and enhanced by repeated immunization or infection with WT SARS-CoV-2. Immunity against all SARS-CoV-2 proteins by CDO-7N-1 should improve efficacy against future SARS-CoV-2 variants. Current SARS-CoV-2 vaccines require several injections for optimal immune protection. Here, the authors report an intranasal live-attenuated vaccine that induces long-term immunity following a single dose and protects from SARS-CoV-2 wildtype and variants in non-human primate and small animal models.